Disciplining Geopolitics: Latin America, the Russia-Ukraine War, and Connected Spaces of (Non-)Intervention Between Anti-Imperial Heritage and Schmittian Decay - Loefflad, Eric (Polish Review of International and European Law, 2025)
The term ‘geopolitics’ often raises a great deal of disdain amongst international lawyers. However, in the face of so many seeming erosions of international legal standards, especially as they concern the principle of non-intervention, some form of engagement with geopolitical realities is essential. In assessing the prospects for analysing international law generally, and the non-intervention norm specifically, through the lens of ‘critical geopolitics’, I take as my starting point the paradox of general neutrality amongst Latin American states regarding Russia’s invasion of Ukraine. While seemingly out of place given the importance of Latin American contributions to the non-intervention norm, I argue that this disjuncture provides an opportunity to explore how geopolitical frameworks in the form of Carl Schmitt’s Grossraum theory and John Mearsheimer’s Neorealism play important roles in constructing international legal consciousness. In doing so, I aim to show how, despite possessing incentives for remaining neutral on Ukraine, Latin America has historically shared a similar intervention-defined fate to Central Eastern Europe that is likely to increase in the future. Through this process of mapping, I hope to open the door for theorisation on how recognising mutual similarities might form agency-expanding inter-connection between Latin America and Central Eastern Europe as parallel spaces defined by enduring the subjugation of – and mounting resistance to – the interventions of proximate great powers.